Nomenclatural notes on Macaronesian Micromeria (Lamiaceae) - Puppo, Pamela; Meimberg, Harald; Pérez De Paz, Pedro Luis; Bräuchler, Christian (Phytotaxa, 2017)
Recently, the authors presented a proposal to conserve the names Micromeria varia Bentham (1834: 374) with a conserved type and M. hyssopifolia Webb & Berthelot (1844: 72) against Thymus ericifolius Roth (1800: 50) (Puppo et al. 2014a) to avoid disruption of current usage of these two well established names. This proposal, however, was not recommended by the Nomenclature Committee (Applequist 2016) and subsequently turned down by the General Committee (Wilson 2017). While regretting this decision, we are prepared to accept the taxonomic and nomenclatural implications.